Impact of repeated radiative heat exposure on protective performance of firefighter's protective clothing. (23rd September 2022) - Rathour, Rochak; Das, Apurba; Alagirusamy, Ramasamy
Firefighters rely heavily on their firefighter's protective clothing (FPC) for their safety. The effectiveness of an appropriately engineered turnout suit decreases over time when repeatedly exposed to radiative heat and flame. A measure of durability is the radiative protective performance (RPP) rating, which is influenced by properties like thickness, surface area, and areal density (mass per unit area) of outer shell fabric in multilayered ensembles. Four independent variables were considered: fabric material, pick density, exposure cycles and heat flux intensity. In addition to RPP, changes in the thickness, shrinkage, and mass loss was also tracked. An evaluation of properties was conducted at the end of each cycle to determine the effects of the heat flux (21, 42 and 63 kW/m 2 ), number of exposure cycles (from one to five) and effects of each attribute. Two types of fabrics were used in this study, one made with meta aramid (Nomex® IIIA) yarns in both warp and weft (type-A fabric), and the other made with Nomex® IIIA (warp) and para aramid (Kevlar ® ) (weft) (type-B fabric). Type-A fabrics displayed a greater degree of differentiation in their properties than type-B fabrics. With the same exposure conditions, the thickness, shrinkage, mass loss and RPP gradually increased. A regression analysis conclusively established that pick density significantly affects the performance of the outer-shell fabric used in FPCs. Textile designers may find the results useful for creating more thermo-stable and durable turnout suits in the future.